Potencial geoturístico das quedas d água de Indianópolis/MG - Bento, Lilian Carla Moreira (2010)
The tourism is growing up in last decades and the alternative tourism with its mainly representatives (ecotourism, geotourism, rural tourism and the adventure tourism) is which has more highlights actually. Based on this concepts, the geotourism is the more recently, which was created to valorize the non-biotic aspects of the landscape, making a join with contemplation with scientific aspects of the visitation. So, the geoconcervation can be done. In the Triângulo Mineiro it is possible to find rare and good one examples of the geologic patrimony, as the water falls in Indianópolis District. This region is recognized by the variety and by the beauty scenes of its water falls, so the general objective of this research was to identify the potential of this place for the practice of the geotourism. For accomplishing the objectify proposed it was done, in general lines, bibliographic review pertinent to the theme, work field in the rivers (brooks) with water falls and cabinet work, whose step had permitted the integration and analyses of the data obtained and, consequently, results and conclusions presented to the long of this dissertation. With this methodology, among others, it was possible to find and to map 20 water falls in Indianópolis, all with beauty and singular values, exposing in varied size, geologic units which permit the understanding the history of the region geology, as well as the identification of the geomorphologic process actives in the evolution and sculpturing of the water falls. The most part of the fall mapped are located in preserved areas, however, that one more visited show some signs of the degradation, as the deforestation of the vegetation near the fluvial channels, the formation of sediments banks, garbage and erosive process in the ecologic trails. We had conclude that there are great and strong potential of the geotourism related to falls in Indianópolis, mainly that ones named as Salto do Mirandão, Salto de Furnas and Saltinho Santo Antônio. However, to make the implantation of the geotourism in this district, having some benefits to Indianópolis, it is necessary, as a first step, make a tourism planning and create public politics to make the regulation of this activity. So, it will be possible to walk in the direction of sustainable tourism and get one of the proposes of the geotourism, that is environmental conservation.